2018
DOI: 10.1161/circulationaha.117.032882
|View full text |Cite
|
Sign up to set email alerts
|

Response by Fernández-Jiménez et al to Letters Regarding Article, “Dynamic Edematous Response of the Human Heart to Myocardial Infarction: Implications for Assessing Myocardial Area at Risk and Salvage”

Abstract: BACKGROUND: Clinical protocols aimed to characterize the post-myocardial infarction (MI) heart by cardiac magnetic resonance (CMR) need to be standardized to take account of dynamic biological phenomena evolving early after the index ischemic event. Here, we evaluated the time course of edema reaction in patients with ST-segment-elevation MI by CMR and assessed its implications for myocardium-at-risk (MaR) quantification both in patients and in a large-animal model. METHODS: A total of 16 patients with anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Edema is a very dynamic process during the first week after myocardial infarction (24), and strain closely associates with its intensity and volume (20). Moreover, cardioprotective therapies may affect the extent and intensity of post-myocardial infarction edema (25).…”
Section: The Effect Of Metoprolol On Long-term Resultsmentioning
confidence: 99%
“…Edema is a very dynamic process during the first week after myocardial infarction (24), and strain closely associates with its intensity and volume (20). Moreover, cardioprotective therapies may affect the extent and intensity of post-myocardial infarction edema (25).…”
Section: The Effect Of Metoprolol On Long-term Resultsmentioning
confidence: 99%
“…Contrast-enhanced steady state free precession imaging provides superior image quality to T2-weighted imaging and has been validated against SPECT 103 and angiographic scores 104 . Still, there has been some debate regarding the validity of CMR based evaluation of MaR 105,106 and the most appropriate timing for it, considering the bimodal pattern of edema after myocardial infarction [107][108][109][110] . However, a recent study in pigs validated contrast-enhanced steady state free precession imaging and T2-weighted imaging against histopathology to measure MaR seven to ten days after LAD artery occlusion and found good agreement, confirming its applicability in this time frame 111 .…”
Section: Myocardium At Riskmentioning
confidence: 99%
“…Furthermore, myocardial edema determined by CMR has also been argued to correlate better with the extent of myocardial infarction than with MaR 171 . Although these methods are validated and widely used to evaluate MaR, the above mentioned issues have questioned the appropriateness of their use to measure MaR in studies of cardioprotection 105,110,169,170 .…”
mentioning
confidence: 99%
“…This complex tissue-level heterogeneity makes CMR appealing for non-invasive characterisation of myocardial injury after myocardial infarction [3]. Previous studies have demonstrated the utility of undertaking CMR imaging 24-72 h after PPCI, and some as early as few hours after myocardial infarction (MI) [4][5][6]. These studies revealed imaging features most likely reflective of the underlying dynamic tissue-level changes [4,5].…”
Section: Introductionmentioning
confidence: 99%